An Investigation of Shorting Pin Effects on Circular Disc Microstrip Antennas - Dilek UZER; Seyfettin GÜLTEKIN (International Journal of Applied Methods in Electronics and Computers, 2015)
In this study, shorting pin addition, one of the common bandwidth enhancement techniques, is performed on traditional circular disc microstrip antennas that have three different dielectric substrate thicknesses and designed in three different resonant frequencies. Numbers of added shorting pins and positions of these pins are changed in every step, systematically and different pin combinations are tried for three antennas that design parameters are present in literature. Later, optimal pin combinations that give the intended resonant frequencies and the largest bandwidths are determined.  For these optimal combinations, by keeping the resonant frequencies constant, the bandwidths of the antennas are increased to %1.440, %2.780 and % 6.024, respectively. Compared to measurement results in the literature, for bandwidths, significant improvements are obtained. At the same time, it is observed that the technique of shorting pin addition increases the bandwidths in higher percentages on thicker microstrip antennas. For three antennas, it is seen that all pin combinations give similar resonant frequency variations depended on pin positions.